Trigonometry

posted by .

Prove that
sin(n+1)Asin(n-1)A + cos(n+1)Acos(n-1)A = cos2A

  • Trigonometry -

    Let (n+1)A = x
    Let (n-1)A = y
    sinx*siny + cosx*cosy = cos (x - y)
    (This is an identity you should know)
    Now note that x -y = 2A , so

    sinx*siny + cosx*cosy = cos (x - y)
    = cos(2A)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. trig

    Show that 1-cos2A/Cos^2*A = tan^2*A 1-cos2A/Cos^2*A = [Cos^2(A) - Cos(2A)]/Cos^2(A). Substitute: Cos(2A) = 2Cos^2(A) - 1: [1 - Cos^2(A)]/Cos^2(A)= Sin^2(A)/Cos^2(A) = tan^2(A)
  2. tigonometry

    expres the following as sums and differences of sines or cosines cos8t * sin2t sin(a+b) = sin(a)cos(b) + cos(a)sin(b) replacing by by -b and using that cos(-b)= cos(b) sin(-b)= -sin(b) gives: sin(a-b) = sin(a)cos(b) - cos(a)sin(b) …
  3. Math/Calculus

    Please check my work and correct any errors/point out any errors. Thanks. Solve the initial-value problem using the method of undetermined coefficients. y''-4y=e^xcos(x), y(0)=1, y'(0)=2 r^2-4=0, r1=2, r2=-2 yc(x)=c1*e^2x+c2*e^-2x …
  4. Mathematics - Trigonometric Identities

    Let y represent theta Prove: 1 + 1/tan^2y = 1/sin^2y My Answer: LS: = 1 + 1/tan^2y = (sin^2y + cos^2y) + 1 /(sin^2y/cos^2y) = (sin^2y + cos^2y) + 1 x (cos^2y/sin^2y) = (sin^2y + cos^2y) + (sin^2y + cos^2y) (cos^2y/sin^2y) = (sin^2y …
  5. Trigonometry

    Prove the identity sin(x+y+z)+sin(x+y-z)+sin(x-y+z)+ sin(x-y-z) = 4 sin(x)cos(y)cos(z) This identity is so long and after i tried to expand the left side and it just looked something crap Thanks for you help :)
  6. Trigonometry

    Prove that sin(n+1)Asin(n+2)A + cos(n+1)Acos(n+2)A = cosA
  7. Trigonometry

    1.Solve tan^2x + tan x – 1 = 0 for the principal value(s) to two decimal places. 6.Prove that tan y cos^2 y + sin^2y/sin y = cos y + sin y 10.Prove that 1+tanθ/1-tanθ = sec^2θ+2tanθ/1-tan^2θ 17.Prove that …
  8. trigonometry help me

    6.Prove that tan y cos^2 y + sin^2y/sin y = cos y + sin y 10.Prove that 1+tanθ/1-tanθ = sec^2θ+2tanθ/1-tan^2θ 17.Prove that sin^2w-cos^2w/tan w sin w + cos w tan w = cos w-cot w cos w 23.Find a counterexample …
  9. Trigonometry desperate help, clueless girl here

    2. solve cos 2x-3sin x cos 2x=0 for the principal values to two decimal places. 3. solve tan^2 + tan x-1= 0 for the principal values to two decimal places. 4. Prove that tan^2(x) -1 + cos^2(x) = tan^2(x) sin^2 (x). 5.Prove that tan(x) …
  10. math

    cos^6A-sin^6A=cos2A(1-1÷4sin^2 2A) Prove

More Similar Questions